2022
DOI: 10.1038/s41366-022-01090-7
|View full text |Cite
|
Sign up to set email alerts
|

Tissue losses and metabolic adaptations both contribute to the reduction in resting metabolic rate following weight loss

Abstract: Objective To characterize the contributions of the loss of energy-expending tissues and metabolic adaptations to the reduction in resting metabolic rate (RMR) following weight loss. Methods A secondary analysis was conducted on data from the Comprehensive Assessment of Long-term Effects of Reducing Intake of Energy study. Changes in RMR, body composition, and metabolic hormones were examined over 12 months of calorie restriction in 109 individuals. The con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
1
11
0
1
Order By: Relevance
“…This contention is supported by findings from a revisit to the Minnesota Starvation Experiment of a positive relationship between diminished mass‐adjusted resting EE and the degree of fat depletion (but not with the degree of FFM depletion) both during weight loss and weight regain [2]. It is also supported by more recent studies indicating an association between diminished mass‐adjusted EE and the loss of fat mass during caloric restriction [5–7]. These findings are consistent with the concept of two distinct control systems underlying adaptive thermogenesis in response to energy deficit [8].…”
Section: Persistence Of Metabolic Adaptation During Weight Regainsupporting
confidence: 65%
“…This contention is supported by findings from a revisit to the Minnesota Starvation Experiment of a positive relationship between diminished mass‐adjusted resting EE and the degree of fat depletion (but not with the degree of FFM depletion) both during weight loss and weight regain [2]. It is also supported by more recent studies indicating an association between diminished mass‐adjusted EE and the loss of fat mass during caloric restriction [5–7]. These findings are consistent with the concept of two distinct control systems underlying adaptive thermogenesis in response to energy deficit [8].…”
Section: Persistence Of Metabolic Adaptation During Weight Regainsupporting
confidence: 65%
“…Contrary to popular belief, it is not skeletal muscle but rather adipose tissue losses that seem to drive RMR reduction following weight loss [18]. FFM, TBW, and BM values decreased during a three-month program in each group (Table 1.).…”
Section: Anthropometric Characteristicsmentioning
confidence: 73%
“…Investigations [ 36 , 37 ] have shown that a low-carb diet is more effective at reducing visceral fat than a low-fat diet. Furthermore, contrary to popular belief, it is not skeletal muscle but rather adipose tissue losses that seem to drive RMR reduction following weight loss [ 38 ]. Furthermore, Yener et al (2017) [ 39 ] assert that cortisol can increase the visceral fat the body stores so that stress reduction may influence fat loss.…”
Section: Discussionmentioning
confidence: 90%